Economic feasibility analysis of fisherwomen based microenterprises - Hassan, Femeena; Prathap, Sangeetha K; Charles Jeeva, J.; Mathew, Saleena; Remya Babu, M. (Indian Journal of Fisheries, 2013)
Women in fishing communities are major players in the post-harvest sector and are traditionally involved in processing and marketing of fish. The issue of women’s limited control over resources has been discussed widely and there is need to develop micro-level interventions together with macro-level advocacy as a strategy to strengthen women’s role in post-harvest activities and in preparing and marketing of value-added fish products. In marine fisheries, while high value species are mostly processed for export, most of the medium and low value species, which form bulk of the landings, are marketed fresh or processed for the domestic market. Women perform their tasks either at home or as labourers in commercial processing units. However, they fail to realise the benefits to support themselves as well as family. Location-specific and need-based training programmes for fisherwomen can enhance their technical know-how and awareness enabling them to start gainful employment ventures. The economic feasibility of fish based value added items by self help group (SHG) group micro-enterprises is discussed in this paper.